2011
DOI: 10.1177/0267659111409969
|View full text |Cite
|
Sign up to set email alerts
|

2010 Survey on cell phone use while performing cardiopulmonary bypass

Abstract: Cell phone use in the U.S. has increased dramatically over the past decade and text messaging among adults is now mainstream. In professions such as perfusion, where clinical vigilance is essential to patient care, the potential distraction of cell phones may be especially problematic. However, the extent of this as an issue is currently unknown. Therefore, the purpose of this study was to (1) determine the frequency of cell phone use in the perfusion community, and (2) to identify concerns and opinions among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 13 publications
(13 reference statements)
4
52
2
6
Order By: Relevance
“…In the medical industry, for instance (see Gill, Kamath, & Gill, 2012), there have been claims that patient lives have been endangered by doctor inattention caused by smartphone use (Halamka, 2011). A recent survey found that among medical professionals performing cardiopulmonary bypass, a situation in which vigilance is critical for patient safety, 56% have admitted to using their cellphone during surgical procedures (Smith, Darling, & Searles, 2011). When it comes to academic performance, the available evidence suggests that students who use their mobile phones to text or talk while completing schoolwork have poorer educational outcomes than those who do not (Junco & Cotten, 2012), and that ringing phones during a lecture can divide attention and result in poorer recall of lecture material (Shelton, Elliot, Lynn, & Exner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the medical industry, for instance (see Gill, Kamath, & Gill, 2012), there have been claims that patient lives have been endangered by doctor inattention caused by smartphone use (Halamka, 2011). A recent survey found that among medical professionals performing cardiopulmonary bypass, a situation in which vigilance is critical for patient safety, 56% have admitted to using their cellphone during surgical procedures (Smith, Darling, & Searles, 2011). When it comes to academic performance, the available evidence suggests that students who use their mobile phones to text or talk while completing schoolwork have poorer educational outcomes than those who do not (Junco & Cotten, 2012), and that ringing phones during a lecture can divide attention and result in poorer recall of lecture material (Shelton, Elliot, Lynn, & Exner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 19% of residents and 12% of attending physicians acknowledged missing important clinical information because of smartphone distraction during rounds and 34% of residents and 20% of attending physicians reported observing another team member miss important clinical information because of smartphone distraction during in-patient round attendance. Smith et al [8] surveyed surgical technicians about their use of their mobile phones while operating a heart-lung machine. He found that 55.6% self-reported using their mobile phone while working, 49.2% acknowledged sending text messages, 21% accessed personal email, 15.1% browsed the Internet, and 3.1% checked or posted on social networking sites.…”
Section: Introductionmentioning
confidence: 99%
“…This may be exacerbated by the fact that not only are the interns in the current survey receiving work related communication, but as it is a personal phone, they are likely receiving additional personal communications. It has been suggested that smartphone use can also negatively impact the relationship between doctors and nurses,10 lead to unprofessional behaviour,11 interfere with medical equipment,12 and be a possible source of infection 13…”
Section: Discussionmentioning
confidence: 99%